Respostas fisiológicas e bioquímicas em Meloeiro (Cucumis melo L.) inoculado com fungos micorrízicos arbusculares sob estresse salino. - Lúcio, Wilber da Silveira (2008)
The accumulation of salts in the soil is a common problems of arid and semi-arid regions, that cause reduction in plant growth and yield. In this context, the arbuscular mycorrhizal fungi (AMF) have been studied in recent years, with results indicating that their associations with the plants roots minimize some effects of salt stress. The objective of this work was to evaluate the influence of increasing levels of salinity of the irrigation water in the melon plants mycorrhized with AMF. The experiment was carried out at the greenhouse of the Departamento de Ciências dos Solo da Universidade Federal do Ceará, in Fortlaeza, Ceará. The experiment design was completely randomized with treatments outlined following a 2 x 4 factorial design, comprised of two mycorrhiza treatments (inoculated and not inoculated plants) x 4 levels of salinity (CEa = 0.5; 1.5; 3.0 and 4.5 dS m-1), with 4 repetitions. During the experiment were conducted measurements of stomatal conductance, transpiration and photosynthesis rates. The plants were collected thirty-seven days after germination, when growth (dry and leaf area), microbiological traits (dependency and mycorrhizal colonization), mineral content (N, P, K, Ca, Mg, Na, Cl) and the organic solutes concentrations (soluble carbohydrates, N-aminossolúveis and proline) were measured. The mycorrhized plants showed higher production of shoot dry matter and leaf area, in relation to non-inoculated plants, mainly in the treatment of 0.5 dS m-1. However, this beneficial effect decreased in the higher levels of salinity. The stomatal conductance, transpiration rate and photosynthetic rate were influenced by AMF, being the values higher in mycorrhized plants. The organic solutes, proline, N-aminossolúveis carbohydrates soluble, did not contribute directly to the osmotic adjustment of leaf tissue. The symbiotic association between the AMF, and the melon has not provided an increase in tolerance of this culture to salt stress, however helped in lower absorption of potentially toxic ions (Na, Cl) from the salinity of irrigation water 3.0 dS m - 1.